Architectural conservation in Europe and the Americas : national experiences and practice - Stubbs, John H.; Makas, Emily Gunzburger (Hoboken, N.J. : John Wiley & Sons, 2011)
'The first major survey that looks at the conservation of cultural heritage in both Europe and the Americas, this book will serve as a convenient resource for professionals, students, and anyone interested in the field. Following the acclaimed Time Honored, Architectural Conservation in Europe and the Americas presents contemporary practice on a country-by-country and region-by-region basis, facilitating comparative analysis of similarities and differences. Written to'stand alone' from the predecessor volume, this book will be followed by a third and final volume covering Asia, Africa, Oceana, and the Polar Regions'--Provided by publisher.
Includes bibliographical references (p. 675-698) and index.
Keywords: Architecture -- Conservation and restoration -- Europe; Architecture -- Conservation and restoration -- America